Vertically Stacked Broadband GNIF-MoS2/p-Ge Photodetector for Dark Current Suppression, High Photoresponse, and Ultrafast Transient Response - Pandey, Rajiv Kumar; Choi, Hwayong; Kim, Young Hoon; Jeong, Subin; Kim, Yeji; Heo, Junseok (Advanced Optical Materials, 2024)
The proposed model structure, featuring a gold (Au) nano-island film (GNIF) integrated with a vertically stacked van der Waals heterojunction and offering an elegant platform for high-performance, efficient, and sensitive photodetection across a broad spectral range, is designated as GNIF-MoS₂/p-Ge(MoS2 = Molybdenum disulfide, p-Ge = p type germanium). The GNIF is fabricated via ultrathin film deposition, based on the surface dewetting properties of MoS2. The as-fabricated photodetector (PD), offering ≈20 times reduction in dark current and characterized by wavelength-dependent high responsivity (R(λ)), photoconductive gain (G(λ)), and detectivity (D(λ)), respond to a broad spectral range from visible light (400 nm) to short wave infrared (SWIR) (1600 nm). The ultrahigh transient response (τr) is found to be ≈2.5 and 16 µs for the 470 (visible light) and 1550 (SWIR) nm wavelengths, respectively, resulting in 3-dB bandwidths of up to ≈48 kHz, which is considered high for such devices. To understand the inherent mechanisms of broadband detection and the high photoresponse and ultrafast transient response of PDs, a meticulous investigation is conducted on the wavelength-dependent behaviors, depletion width changes, and material properties. The results provide valuable insights and a basis for the construction of suitable PDs based on nanometer-thin metal films, 2D semiconductors, and a 3D hybrid structure.
Keywords: Au nano-island film; Charge transfer interaction; Island films; Metal surface plasmon; Metal surfaces; MoS 2; Nano-islands; P-n heterojunctions; Schottky contacts; Surface-plasmon; Au nano-island film; charge transfer interaction; metal surface plasmons; p-n heterojunction; Schottky contact